THIRD DAY OPENING REMARKS - John Gilmour (The Journal of Intelligence, Conflict and Warfare, 2025)
Dr. Gilmour’s remarks focused on defending sovereignty in an environment that, due to evolving threats, is more complex than ever. Subsequently, a fundamental problem for modern states is defending against threats while maintaining sovereignty. Dr. Gilmour concluded that international cooperation is fundamental to addressing threats, however previous alliances and multilateral institutions, of which Canada is a key contributor and beneficiary, are coming under increased threat.